MANAJEMEN SUPERVISI PENDIDIKAN DI SMK NEGERI 3 YOGYAKARTA - Dhani Febriansyah; Shalwanisa Dini Pratiwi; Aliifah Nahdah Prawesti; Vivian Putri Chamelian; Zalsabilla Putri Sekar Kedhaton (Jurnal Manajemen Pendidikan, 2026)
This study aims to analyze the management of educational supervision at SMK Negeri 3 Yogyakarta, which includes planning, organizing, implementation, evaluation, and follow-up of educational supervision integrated with the Internal Quality Assurance System (IQAS/SPMI). This study employed a qualitative method with a case study approach. Data were collected through interviews involving the Vice Principal for Internal Quality Assurance as the main participant. The collected data were analyzed descriptively through data reduction, data presentation, and conclusion drawing. The findings revealed that the management of educational supervision at SMK Negeri 3 Yogyakarta has been implemented systematically through administrative supervision, classroom observation, data-based evaluation, and management review. The supervision process is also supported by teacher competency development workshops based on Artificial Intelligence (AI), the use of digital performance assessment systems, and the involvement of Learning Communities as peer supervisors. In addition, humanistic and collaborative approaches are applied in the supervision process to support teachers in improving their professional competencies. However, several challenges were identified, including limited supervision schedules and the difficulties experienced by senior teachers in preparing digital-based learning administration. The novelty of this study lies in the integration of educational supervision management with the Internal Quality Assurance System (SPMI), the utilization of Learning Communities as peer supervisors, and the implementation of humanistic and digital transformation approaches in vocational school supervision.